Twitter as a catalyst for transforming geography teacher education - Kudzayi Savious Tarisayi (ARKA INSTITUTE, 2024)
This study explored the potential of Twitter to transform and enrich geography teacher education in South Africa for the digital age. This mixed methods study utilized content analysis of tweets from selected geography education Twitter handles and focus group discussions with South African student teachers using Twitter. The research design involved training student teachers on using Twitter for curriculum purposes over eight weeks, followed by focus groups to capture their experiences and perspectives. Findings suggest Twitter offers valuable opportunities for networking, accessing resources, and fostering global connections among geography educators. However, realizing Twitter's full potential requires thoughtful implementation strategies, including usage policies, educator training, and support for community building. As an exploratory study, it provides initial evidence that integrating Twitter into teacher training could strengthen geography education in South Africa by equipping educators with expanded networks and professional development avenues. Nevertheless, structured implementation and ongoing collaboration are crucial for leveraging Twitter to bridge divides and align training with 21st-century contexts. Further comparative and longitudinal studies can build on these preliminary insights to optimize the use of Twitter in transforming geography education for the digital age in South Africa and beyond.